2003
DOI: 10.1046/j.1444-2906.2003.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal denaturation and autolysis profiles of myofibrillar proteins of mantle muscle of jumbo squid Docidicus gigas

Abstract: Jumbo squid was very similar to Japanese common squid in terms of myofibrillar Ca2+‐, Mg2+‐ and K+(EDTA)‐ATPase activities. Myofibrils of jumbo squid were significantly stabilized upon addition of Ca2+ and destabilized by increasing KCl concentration for heating. Incubation of muscle homogenate of jumbo squid induced a selective cleavage of myosin into two major fragments and the cleavage was inhibited by EDTA. Autolysis was prominent at and above 0.3 M NaCl where myosin filaments dissolve. The enzyme involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 15 publications
3
23
0
7
Order By: Relevance
“…This can indicate that myosin in the AM and F muscles can be degraded by proteolytic enzymes. Konno et al [25] also reported that myosin was the major target protein for proteinases and that the proteolytic activity remained unchanged during frozen storage.…”
Section: Resultsmentioning
confidence: 99%
“…This can indicate that myosin in the AM and F muscles can be degraded by proteolytic enzymes. Konno et al [25] also reported that myosin was the major target protein for proteinases and that the proteolytic activity remained unchanged during frozen storage.…”
Section: Resultsmentioning
confidence: 99%
“…Por otra parte, es bien conocido que el mu´sculo del manto de calamar (Dosidicus gigas) al igual que otras especies contiene enzimas proteolı´ticas que degradan las mole´culas de miosina en fragmentos ma´s cortos, una enzima proteolı´tica que rompe la mole´cula de miosina en fragmentos de meromiosina pesada y meromiosina ligera (MML) y otra que rompe la miosina en subfragmentos S-1 y varilla (Konno, Young-ie, Yoshioka, Shinho, & Seki, 2003). Sa´nchez et al (2007), obtuvieron un concentrado proteico a partir de manto de calamar (Dosidicus gigas) y evaluaron la autolisis de las proteı´nas en un periodo de 24 horas a 2-5 8C, observaron que la CPM decrecio´en un 93% durante las primeras 2 horas y desaparecio´completamente despue´s de 24 horas de almacenamiento.…”
Section: Perfil Electrofore´ticounclassified
“…The sarcoplasmic fraction contains enzymes, such as proteases, which act on myosin, producing HMM and LMM, while other enzymes cleave myosin subfragments S1 and S2. It is believed that this degradation leads to deterioration of the thermal gel (Konno, Young-Je, Yoshioka, Shinho, & Seki, 2003;Nagashima, Ebina, Nagai, Tanaka, & Taguchi, 1992). Furthermore, other myofibrillar proteins, such as actin, regulatory and cytoskeletal proteins, do not form gels.…”
Section: Thermal Gelation Of the Myofibrillar Proteins Of Aquatic Orgmentioning
confidence: 99%